Uncovering Students' Learning Styles in Biology Lessons Based on Gender in Senior High Schools in Jeneponto District - Rahmat Saleh; Filawati Filawati (Biology Teaching and Learning, 2023)
Abstract. One of the important things that must be considered by the teacher in the learning process is to know in advance the characteristics of students. Learning style modality is one of how students know and recognizes their personality in the learning process. The type of research used in this study was a survey using a qualitative descriptive approach. The population in this study were all high school students in class IX, Jeneponto Regency, for the 2021/2022 academic year. The samples in this study were students from SMA 9, SMA 10, and SMA 12 students in class IX. science specialization with a total of 67 students consisting of 20 male students and 47 female students. The instrument used in this study was the VARK questionnaire (Visual, Aural, Read, and Kinesthetic) developed by Neil D. Fleming. Data were analyzed using descriptive analysis with the acquisition of the percentage of each learning style possessed by students. The results showed that the modality of the learning styles of Jeneponto District Senior High School students was the Aural learning style. There is no difference in learning styles between male and female students. The dominant gender based student learning style is Aural. .Keywords: biology lessons, learning styles, gender.